Investigating the relationship between social responsibility and financial performance, financial stability and financial inclusion of banks admitted to the Tehran Stock Exchange - Seyfideli, Akram; FarhadTouski, Omid (International Journal of Business Management and Entrepreneurship, 2024)
Corporate social responsibility is a strategic decision whereby committed organizations can help solve environmental and social issues with the aim of positively affecting people outside the organization. The importance of financial and non-financial performance of companies is an undeniable issue for organizations as well as social responsibility. Based on this, this article examines the effect of corporate social responsibility on financial performance, participation or financial inclusion and financial stability of banks admitted to the Tehran Stock Exchange during the period 2015 to 2022. The results show that social responsibility has a significant effect on all three dependent variables, so that the ratio of tax to total assets has a positive effect on financial performance (return on assets, return on equity, and net profit margin) and a negative effect on the financial inclusion of banks. The effect of the ratio of the number of employees to total assets also has a negative effect on financial performance, financial stability and financial inclusion